Power Flow Regulation of PLTS and Genset in Residential Using PLC Zelio - Kusmantoro, Adhi; Farikhah, Irna (Jambura Journal of Electrical and Electronics Engineering, 2025)
At this time many homes are in dire need of a source of electricity. In addition, the electricity source comes from fossil fuels, the availability of which is decreasing. One of the abundant renewable energy sources is solar energy. In the study, it was proposed to regulate PLTS and Genset in residential using PLC Zelio. The purpose of this study is to regulate the power flow to residential loads, so that the power flow to the load is not interrupted. The method used is with the stages of identifying solar irradiation, calculating the load, planning PLTS and designing a power regulator. For PLTS planning, it includes solar panels, batteries, battery charge controller or solar charge controllers, and inverters. The number of solar panels needed is 4 from 250 Wp solar panels. When the battery is used with a lower limit energy of state of change (SOC) of 50%, the number of batteries needed is 8. Based on the calculation, the SCC capacity used is 50 A. The study results show the regulation of energy flow with PLTS and Genset sources on residential loads. In addition, the abundant solar energy sources in the city of Semarang can be utilized for power generation using solar panels.Saat ini, banyak rumah tinggal yang sangat membutuhkan sumber listrik, Selain itu sumber listrik berasal dari energi fosil yang ketersediannya semakin berkurang. Salah satu sumber energi terbarukan yang melimpah adalah energi matahari. Dalam penelitian diusulkan pengaturan PLTS dan genset pada rumah tinggal menggunakan PLC Zelio. Tujuan dalam penelitian ini adalah mengatur aliran daya pada beban rumah tinggal, sehingga aliran daya ke beban tidak terputus. Metode yang digunakan dengan tahapan mengidentifikasi iradiasi matahari, menghitung beban, merencanakan PLTS dan mendesain pengatur daya. Untuk perencanaan PLTS meliputi panel surya, baterai, pengatur pengisian baterai atau solar charge controller, dan inverter. Jumlah panel surya yang dibutuhkan sebanyak 4 buah dari panel surya 250 Wp. Ketika baterai digunakan dengan batas bawah energi atau state of change (SOC) 50% maka jumlah baterai yang dibutuhkan sebanyak 8 buah. Berdasarkan perhitungan terlihat kapasitas SCC yang digunakan sebesar 50 A. Hasil studi memperlihatkan pengaturan aliran energi dengan sumber PLTS dan Genset pada beban rumah tinggal. Selain itu sumber energi matahari yang melimpah di kota Semarang dapat dimanfaatkan untuk pembangkit listrik memakai panel surya.